Insect Physiology - Beard, Raimon L. [et al.]; Edited by Roeder, Kenneth D. (New York John Wiley & Sons, Inc., 1953)
Structure and function of the integument; Chemical and physical properties of cuticle; The penetration of substances through the cuticle; Respiratory mechanisms; Respiratory metabolism; Physical properties and chemical composition of insect blood; The internal environment in regulation and metamorphosis; The hemocytes, pericardial cells, and fat body; Circulation; Structure of the alimentary system; Functions of the alimentary system; The mechanism of digestion; Function of the gut in absorption, excretion and intermediary metabolism; Nutrition; Excretion; The biochemistry of muscle; Electric activity in nerves and ganglia.
Include Figures, Tables, Bibliography and Index.
Keywords: Insects--Physiology -- Physiology, Insects